Artificial flood reduces fine sediment clogging enhancing hyporheic zone physicochemistry and accessibility for macroinvertebrates. Issue 4 (29th October 2021) - Mathers, Kate L.; Robinson, Christopher T.; Weber, Christine
Abstract: River regulation globally has reduced the riverine connectivity (longitudinal, lateral and vertically) with significant consequences for their abiotic and biotic components. To restore the ecological integrity of regulated rivers, artificial floods are increasingly being employed in large‐scale flow restoration efforts. Despite considerable recognition regarding the ecological and geomorphological effects of artificial floods on benthic habitats, understanding the implications for the hyporheic zone is essentially absent. This void in our management knowledge base is considerable given that one of the most widely associated consequences of flow regulation is excessive deposition of fine sediment (sedimentation; particles <2 mm) that often disconnects the hyporheic zone from surface waters. In this study, we examined the effects of an artificial flood on the hyporheic zone of the River Spöl in Switzerland. Fine sediment content of shallow benthic substrates (ca. 10 cm) was significantly reduced following the flood. The flushing of fine sediment was also apparent in hyporheic substrates (depths of 0.25 and 0.50 m), resulting in a reconnection of previously clogged interstitial pathways. The opening of interstitial pore space enhanced physicochemical conditions in the hyporheic zone, such as improved dissolved oxygen concentrations, and supported greater taxa richness. Alterations in the composition of shallower hyporheic assemblages (0.25 m) were evident following the flood. These results indicated that benthic pore space became more connected to surface waters following the flood, thereby enhancing accessibility for interstitial organisms. Our results suggest that artificial floods can be an effective management tool to restore spatial heterogeneity in sediment composition and pore space and improve vertical connectivity for macroinvertebrates. We anticipate that artificial floods would be required on a regular basis given the re‐accumulation of fine sediment 10 months later in our study system. We encourage river managers and scientists to consider flow disturbance and restoration in a holistic manner that encompasses the multiple spatial dimensions of connectivity, including the hyporheic ecotone. Abstract : We examined the effects of an artificial flood on the hyporheic zone of the River Spöl in Switzerland. Immediately following the flood, the fine sediment content of the riverbed was reduced, resulting in enhanced physicochemical conditions in the hyporheic zone. We also observed enhanced utilization of the hyporheic zone by macroinvertebrates suggesting there had been a reconnection of previously clogged interstitial pathways with surface waters. We anticipate that artificial floods would be required on a regular basis given the re‐accumulation of fine sediment 10 months later in our study system.